Association between red cell distribution width–and–albumin ratio and the risk of peripheral artery disease in patients with diabetes - Li, Dongling; Long, Juan; Zhang, Jialu; He, Meinan; Zeng, Qingxiang; He, Qiaoling; Zhan, Wanhua; Chi, Yongqian; Zou, Mengchen (Frontiers in Endocrinology, 2024)
Aim The aim of this study is to explore the association between red blood cell distribution width–to–albumin ratio (RAR) and the risk of peripheral artery disease (PAD) in patients with diabetes. Methods This cross-sectional study extracted the data of 1,125 participants with diabetes from the National Health and Nutrition Examination Survey database. A weighted univariable logistic regression model was used to explore variables associated with PAD. With PAD as the outcome variable, a weighted logistic regression model was established. The odds ratio (OR) and 95% confidence interval (CI) were effect size. Results After adjusting for covariates, the risk of PAD in patients with diabetes was observed in those with higher RAR (OR = 1.83; 95% CI: 1.06–3.15). In addition, RAR ≥3.25 was related to increased risk of PAD in patients with diabetes (OR = 2.04; 95% CI: 1.05–3.95). In people with diabetes aged ≥65, RAR was a risk factor for PAD with an OR value of 2.67 (95% CI: 1.30–5.46). RAR ≥3.25 was associated with increased risk of PAD (OR = 3.06; 95% CI: 1.15–8.11) relative to RAR <2.80. In people with diabetes who smoked, the risk of PAD was elevated in those with RAR ≥3.25 (OR = 2.85; 95% CI: 1.28–6.32). As for patients with cardiovascular disease, the risk of PAD was elevated as the increase of RAR (OR = 2.31; 95% CI: 1.05–5.10). RAR ≥3.25 was correlated with increased risk of PAD (OR = 3.75; 95% CI: 1.42–9.87). The area under the curve of RAR for the risk of PAD in patients with diabetes was 0.631 (95% CI: 0.588–0.675). Conclusion A higher RAR was related to increased risk of PAD in patients with diabetes. The findings might offer a reference for the management of PAD in patients with diabetes.